Handbook of transportation engineering - Kutz, Myer. (New York : McGraw-Hill, 2011)
'Transportation Engineering Handbook is the most complete resource available covering all varieties of transportation systems, including freight, passenger, and mass transit, and air, rail, road, and water systems at the local, regional, national, and international levels. This authoritative work provides problem-solving engineering tools, planning, and design techniques with examples of successful applications'--Provided by publisher.
v. 1. Systems and operations -- v. 2. Applications and technologies.
Includes bibliographical references and index.
Keywords: Transportation engineering -- Handbooks, manuals, etc; Traffic engineering -- Handbooks, manuals, etc